On polynomial semantics for propositional logics. Issue 2 (2nd April 2016) - Agudelo-Agudelo, Juan C.; Agudelo-González, Carlos A.; García-Quintero, Oscar E.
Abstract : Some properties and an algorithm for solving systems of multivariate polynomial equations over finite fields are presented. It is then shown how formulas of propositional logics (particularly of finite-valued logics and paraconsistent logics) can be translated into polynomials over finite fields in such a way that several logic problems are expressed in terms of algebraic problems. Consequently, algebraic properties and algorithms can be used to solve the algebraically-represented logic problems. The methods described herein combine and generalise those of various previous works.